Chlorine Decay Simulation in Water Distribution System Using EPANET - Muhammad, Nur Shazwani; Siew, Ming Shin; Abdullah, Jazuri; Abdullah, Jazuri (International Journal of Integrated Engineering, 2021)
Chlorine is used as a disinfectant in the water treatment process so that treated water is delivered safely to consumers. However, chlorine concentration decays when water flows from the treatment plant to the supply point, due to the reaction with natural organic matter and the inner surface of the pipe. Low chlorine concentration may encourage bacteria re-growth, while high chlorine concentration can result in the formation of harmful chemical components. Therefore, this study aims to simulate the complex process of chlorine decay using EPANET. This exercise enables the determination the chlorine concentration dosage required to maintain the desired requirement given by the World Health Organization (WHO) and the Ministry of Health, Malaysia (MOH). A successful model with an extended period of simulations of 72 hours enable the mapping of spatial and temporal variations of flow and residue chlorine concentrations at all links and nodes. Constant chlorine dosage of 3.96 mg/l at node R1 has successfully satisfy the requirement given by WHO and MOH. The residue chlorine concentrations at the nodes and links in the water distribution system also depends on the water usage at node 5, the size of service reservoir and service tank and distance from the reservoir.